EU, Climate Change and Arctic Security Matters - Marinai (2018)
The effects of climate change and, in particular, global warming with the consequent ice melting, have underlined the strategic role of the Arctic region for the European Union. Easier access to raw materials and potential growth in intercontinental maritime traffic are some of the positive effects that climate change may imply. In parallel with such effects, climate change might produce several negative consequences in terms of security. The aim of this article is to assess whether EU action can be deemed suitable for responding to the challenges of climate change and, in particular, to their impact on Arctic security. Firstly, the impact of climate change on the Arctic is considered. Second, the impact of climate change on Arctic security issues is discussed. Then, what the EU has done, or can do to limit climate change and to address Arctic security is examined, while stressing the need for the EU to develop its Arctic policy through a careful and balanced approach.